2016
DOI: 10.1038/srep39644
|View full text |Cite
|
Sign up to set email alerts
|

Beef and coal are key drivers of Australia’s high nitrogen footprint

Abstract: Anthropogenic release of reactive nitrogen (Nr; all species of N except N2) to the global nitrogen (N) cycle is substantial and it negatively affects human and ecosystem health. A novel metric, the N footprint, provides a consumer-based perspective for Nr use efficiency and connects lifestyle choices with Nr losses. Here we report the first full-scale assessment of the anthropogenic Nr loss by Australians. Despite its ‘clean and green’ image, Australia has the largest N footprint (47 kg N cap−1 yr−1) both in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Most papers about N footprints are also based on the N-Calculator methodology , Leach et al 2012, Pierer et al 2014, Shibata et al 2014, Stevens et al 2014, Liang et al 2016, Shibata et al 2017, Hutton et al 2017, which facilitate comparison. Here, we compare only the N footprint of food, as we did not consider the N footprint related to energy consumption.…”
Section: Comparison With Other Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most papers about N footprints are also based on the N-Calculator methodology , Leach et al 2012, Pierer et al 2014, Shibata et al 2014, Stevens et al 2014, Liang et al 2016, Shibata et al 2017, Hutton et al 2017, which facilitate comparison. Here, we compare only the N footprint of food, as we did not consider the N footprint related to energy consumption.…”
Section: Comparison With Other Countriesmentioning
confidence: 99%
“…N footprint is a powerful method that links consumers with their environmental impacts Leach 2016, Galloway et al 2014). Per capita N footprints have been calculated for the US, Netherlands, Japan, Germany, Austria, the UK, Australia and Tanzania, using the N-Calculator model (Leach et al 2012, Shibata et al 2014, Stevens et al 2014, Pierer et al 2014, Liang et al 2016, Hutton et al 2017. N footprints have also been calculated for China and the EU using different approaches (Gu et al 2013, Cui et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The food N footprint of oil palm products calculated in the present study was compared with previously reported N footprints of several countries and the world average (Gu et al 2013, Pierer et al 2014, Shibata et al 2014, Stevens et al 2014, Liang et al 2016, Oita et al 2016, Hutton et al 2017, Shindo and Yanagawa 2017, Hayashi et al 2018 (table 3). The food N footprint of oil palm products in these countries ranged from 0.07 to 0.18 kg N capita -1 yr -1 , whereas their food N footprint ranged from 8.9 to 32 kg N capita -1 yr -1 .…”
Section: Food Nitrogen Footprint Of Oil Palm Productsmentioning
confidence: 86%
“…For example, the consumer-oriented N-Calculator model by Leach et al (2012) estimates the reactive N released to the environment on a per capita basis related to food production and consumption, household utilities, transportation, and the purchase of goods and services. National per capita N footprints have been calculated for more than 10 countries and vary between 15 and 47 kg N capita −1 yr −1 (Pierer et al 2014, Shibata et al 2014, Stevens et al 2014, Liang et al 2016, Shibata et al 2017, Guo et al 2017, Elrys et al 2019. Typically, these studies have emphasized the role of food production (e.g.…”
Section: Introductionmentioning
confidence: 99%